2019
DOI: 10.1128/jvi.01178-19
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Pressure on H3N2 Influenza Virus Drift Strains Imposes Constraints on Binding to Sialylated Receptors but Not Phosphorylated Glycans

Abstract: Influenza subtype H3N2 viruses have circulated in humans for over 50 years, continuing to cause annual epidemics. Such viruses have undergone antigenic drift in response to immune pressure, reducing the protective effects of preexisting immunity to previously circulating H3N2 strains. The changes in hemagglutinin (HA) affiliated with drift have implications for the receptor binding properties of these viruses, affecting virus replication in the culture systems commonly used to generate and amplify vaccine stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Several 2,3-and 2,6-sialylated biantennary N-glycans were identified to be positively bound by influenza strains, which was an exciting development for studying endogenous glycan ligands. This led to the broad screening of various strains of influenza viruses, including these H3N2 strains that have progressively undergone "antigenic drift" in their head domains (Byrd-Leotis et al, 2019a) Surprisingly, the H3N2 drift strains almost completely lost their capacity in binding of canonical sialylated N-glycans on the sequence-defined N-glycan array (Byrd-Leotis et al, 2019a). Moreover, the discoveries with the pig lung glycan array opened the door to later studies with actual human lung tissue to search for endogenous receptors for influenza viruses (Byrd-Leotis et al, 2019b).…”
Section: Discovery Of Natural Glycan Ligands Involved In Infection Anmentioning
confidence: 99%
“…Several 2,3-and 2,6-sialylated biantennary N-glycans were identified to be positively bound by influenza strains, which was an exciting development for studying endogenous glycan ligands. This led to the broad screening of various strains of influenza viruses, including these H3N2 strains that have progressively undergone "antigenic drift" in their head domains (Byrd-Leotis et al, 2019a) Surprisingly, the H3N2 drift strains almost completely lost their capacity in binding of canonical sialylated N-glycans on the sequence-defined N-glycan array (Byrd-Leotis et al, 2019a). Moreover, the discoveries with the pig lung glycan array opened the door to later studies with actual human lung tissue to search for endogenous receptors for influenza viruses (Byrd-Leotis et al, 2019b).…”
Section: Discovery Of Natural Glycan Ligands Involved In Infection Anmentioning
confidence: 99%
“…For example, the inhibition of human anti-N9 antibodies to influenza neuraminidases was analyzed by glycan array [ 70 ]. The binding study of the H3N2 influenza viruses using glycan microarrays demonstrated the changes in virus hemagglutinin that affect the receptor binding properties of the viruses [ 71 ].…”
Section: Elucidation Of the Molecular Basis Of N mentioning
confidence: 99%
“…As synthetic arrays printed with synthetic, well‐defined glycans came into use, it became clear that not only the SA linkage, but also the structural attributes of the underlying glycan are important (Ji et al, 2017; Stencel‐Baerenwald et al, 2014). Many of these studies were performed with the Center for Disease Control (CDC) or Consortium for Functional Glycomics (CFG) (Amonsen et al, 2007; Bradley et al, 2011; Tappert, Smith, & Air, 2011; Gulati et al, 2013, 2014; Walther et al, 2013; Jernigan & Cox, 2015; Pappas et al, 2015; Pulit‐Penaloza et al, 2017; Hosoda et al, 2018; Byrd‐Leotis et al, 2019a) arrays. Detection of binding on arrays has been through direct labeling with fluorophore or through secondary detection with labeled antibody.…”
Section: Revealing the Host Side Of Viral Glycomicsmentioning
confidence: 99%
“…Natural glycan arrays, also known as shotgun arrays, have been constructed from host tissues including swine (Byrd‐Leotis et al, 2014) and human (Byrd‐Leotis et al, 2019a). If collected in sufficient quantities, fractions containing glycans of interest can be revisited and analyzed in more depth.…”
Section: Revealing the Host Side Of Viral Glycomicsmentioning
confidence: 99%